Pemberdayaan Masyarakat Melalui Ekowisata Mangrove (Suatu Kajian di Kawasan Hutan Mangrove Wonorejo, Kecamatan Rungkut, Pantai Timur Surabaya) - Pricillia Azhani; Moh. Hasroel Thayib; Hadi S. Alikodra (Bumi Lestari Journal of Environment, 2019)
Implementation of mangrove ecotourism development which is not suitable with ecotourism concept namely conservation and improvement of people's well-being, so that people can not increase their capacity for social, economic, and ecological independence. The research problems is the lack analysis of communities empowerment through Ecotourism Mangrove Wonorejo (EMW) activities. The main purpose of this study to analyze the communities empowerment through Ecotourism Mangrove Wonorejo (EMW) activities. This research use a quantitative approach with a qualitative and quantitative methods. Data collection instrument are using questionnaire, interview guides, and field observations with tabulation and descriptive analysis. The research results of social empowerment, respondents attend socialization and self improvement training qualification 88% and 83% of respondents simply do the task without any participation in the management and monitoring of EMW activities, in economic empowerment 100% of respondents earn increased revenue but can not create new job opportunities in EMW activities, in ecology empowerment, respondents do not recycle plastic waste, do not process organic waste, and do not conduct electricity and water efficiency (0%). The conclusion is the community do not yet have the ability to make decisions and implement decisions to achieve the goal of public welfare.